Developmental timing of initial racial discrimination exposure is associated with cardiovascular health conditions in adulthood. Issue 7 (3rd October 2021) - Cuevas, Adolfo G.; Ho, Thao; Rodgers, Justin; DeNufrio, Danielle; Alley, Lindsey; Allen, Jennifer; Williams, David R.
ABSTRACT: Objective: To examine the association between developmental timing of initial exposure to racial discrimination and cardiovascular health conditions. Design: Using data from the 1995 Detroit Area Study, logistic and negative binomial regression models were used to assess the association between timing of initial exposure to racial/ethnic discrimination, classified as early childhood (0-7), childhood (8-12), adolescence (13-19), and adulthood (>19), on physician-diagnosed cardiovascular health conditions during adulthood. Each analysis adjusted for age, gender, race/ethnicity, income, education, marital status, health-related behaviors, and pre-existing health conditions. Results: Of the 1, 106 participants in the final sample, 520 identified as White and 586 identified as Black. Over half (64%) of the sample experienced at least one major cardiovascular health event at the time of the study, with 39% reporting two or more events. Results from logistic regression models showed that initial exposure to racial discrimination during early childhood was associated with a 2.96 (95%CI:1.15, 7.83) times greater odds of having any cardiovascular-related health condition later in life compared to individuals who reported no discrimination. Results from negative binomial regression models demonstrated that individuals who reported initial exposure to racial discrimination during early childhood and adolescence had a CVD incidence rate that was 1.63 (95%CI:1.11, 2.38) and 1.37 (95%CI:1.10, 1.69) times higher than individuals who reported no discrimination. Conclusion: Initial exposure to racial discrimination in early childhood and adolescence may increase the risk of cardiovascular conditions later in life. Clinicians and researchers should consider racial discrimination during childhood as a possible risk factor for illness and disease.